1999
DOI: 10.1096/fasebj.13.1.143
|View full text |Cite
|
Sign up to set email alerts
|

Inverse regulation of lipid‐peroxidizing and hydroperoxyl lipid‐reducing enzymes by interleukins 4 and 13

Abstract: 12/15-lipoxygenases and phospholipid hydroperoxide glutathione peroxidases are opposite enzymes balancing the intracellular concentration of hydroperoxy lipids. We studied the regulation of both enzymes by interleukins 4 and 13 and found an inverse response. When human lung carcinoma cells A549 were cultured in vitro in the presence of these cytokines, an up-regulation of the 12/15-lipoxygenase and a down-regulation of the phospholipid hydroperoxide glutathione peroxidase were observed. A similar inverse regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 59 publications
3
39
0
Order By: Relevance
“…Other cytokines, such as IFN-g, IL-6 and IL-10 did not induce the enzyme. 90,91 Experiments with human epidermoid carcinoma A431 cells that were transfected with the cDNA sequence of cytoplasmic PH-GPx revealed that PH-GPx downregulates the 12-LOX activity. 92 In animals, platelets 12-LOX, 15-LOX and COX-2 are more sensitive to PH-GPx inhibition than do 5-LOX and COX-1, which are more resistant.…”
Section: Sources Of Free Radicals During Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Other cytokines, such as IFN-g, IL-6 and IL-10 did not induce the enzyme. 90,91 Experiments with human epidermoid carcinoma A431 cells that were transfected with the cDNA sequence of cytoplasmic PH-GPx revealed that PH-GPx downregulates the 12-LOX activity. 92 In animals, platelets 12-LOX, 15-LOX and COX-2 are more sensitive to PH-GPx inhibition than do 5-LOX and COX-1, which are more resistant.…”
Section: Sources Of Free Radicals During Inflammationmentioning
confidence: 99%
“…When the human lung carcinoma cell line A549 is exposed to IL-4 and 13, an upregulation of the 12/ 15-LOX and a downregulation of the PH-GPx are observed. 90,91 Mitochondrial PH-GPx protects from cell death induced by phospholipid hydroperoxidation triggered by photodynamic therapy. 97 Likewise, 2 arsenic compounds, arsenic trioxide and arsenic disulfide, employed against acute promyelocytic leukemia, induce apoptosis in leukemia cells 98 by inhibiting PH-GPx expression.…”
Section: Sources Of Free Radicals During Inflammationmentioning
confidence: 99%
“…Thus, antioxidant effectors could influence the multiple intracellular events that involve ROS production. Supporting this is that Schnurr et al (67) reported that IL-4-and IL-13-treated A549 cells up-regulate 12/15-lipoxygenase and down-regulate PHGPx, resulting markedly increased levels of endogenous lipid peroxides. They suggested that the generation of hydroperoxides and peroxide-reducing enzymes is inversely regulated.…”
Section: Supplementation Of Lipid Hydroperoxides In Phgpx-overexpressmentioning
confidence: 83%
“…In fact, we observed a significant decrease in cellular glutathione content and increased ratio between oxidized and reduced glutathione in peripheral endothelial cells exposed to this fatty acid [20]. In addition to linoleic acid-induced activation of NF-KB, we have evidence that treatment with this fatty acid can markedly stimulate NF-«B-dependent transcription [14,44]. However, our earlier reports on vascular effects of linoleic acid have been based on cells isolated from major vascular vessels, such as pulmonary artery [14,20,33,38,44] or urn-bilical veins [22,32,34].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to linoleic acid-induced activation of NF-KB, we have evidence that treatment with this fatty acid can markedly stimulate NF-«B-dependent transcription [14,44]. However, our earlier reports on vascular effects of linoleic acid have been based on cells isolated from major vascular vessels, such as pulmonary artery [14,20,33,38,44] or urn-bilical veins [22,32,34]. It is well known that endothelial cells from different tissues and vessels can differ markedly in their structure and functions [45].…”
Section: Discussionmentioning
confidence: 99%